THE UNIQUE DIFFERENT FEATURES OF VOCABULARY OF THE BRITISH ENGLISH (BRE) AND AMERICAN ENGLISH (AME): A REVIEW - Dirgeyasa, I Wy (Universitas Negeri Semarang, 2015)
It is a fact that there are some amazing differences between British English (BrE) and American English (AmE) such as spelling, meaning, pronunciation, usage, and even vocabulary. The two varieties of English, as a matter of fact, are often confusing especially who study and use English as second and foreign language. Because of their differences and distinctive features, the speakers often find difficulties which one to use. This condition, then can lead to misunderstanding and misinformation and this finally causes ineffective communication.Â This paper is attempting to review the unique features of BrEandÂ AmEfocusing on the vocabulary.